Pengaruh Kesadaran Wajib Pajak, Pengetahuan, Sistem Adminitrasi Perpajakan Modern, dan Sanski Pajak Terhadap Kepatuhan Perpajakan Pada Kantor Pelayanan Pajak Madya Makassar - Wahyuni Wahyuni (STIEM BONGAYA, 2018)
This study aims: (1) To analyze the effect of taxpayer awareness on taxpayer compliance at Makassar Middle KPP. (2) Analyzing the effect of taxation knowledge on taxpayer compliance at Makassar Middle KPP. (3) Analyzing the effect of the modern tax administration system on taxpayer compliance at Makassar Middle KPP. (4) Analyze the effect of tax sanctions on taxpayer compliance at Makassar Middle KPP. The variables used in this study are taxpayer awareness (X1), taxation knowledge (X2), modern tax administration system (X3), tax sanction (X4), taxpayer compliance (Y). Research conducted by looking at taxpayer compliance from aspects of legal entity, type of business and length of establishment of business. The sample technique used with purposive sampling so that 92 samples of taxpayers were obtained. Data testing method uses multiple regression analysis with the help of SPSS version 22.00. Based on the results of testing the data obtained that the awareness of taxpayers, knowledge of taxation, tax administration system and tax sanctions have a positive and significant effect on taxpayer compliance at Makassar Middle KPP.